Problem Based Learning dan Argumentation Sebagai Solusi dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SMK - Sudirman Rizki Ariyanto; Ikke Wulan Puji Lestari; Savira Uswatun Hasanah; Latifahtur Rahmah; Devi Vitriana Purwanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This study is aimed to analyze advantages of problem based learning and argumentation (PBLA) for vocational school students; and (2) analyze the implementation of PBLA to improve the critical thinking skills of vocational school students. This was library research which used secondary data sources and were collected through scientific articles, books, websites, and other relevant sources. Furthermore, the data were analyzed qualitatively with the Miles and Huberman model, which consisted of data collection, data reduction, data presentation, and concluding. From the results of the literature study, several conclusions can be drawn which include: (1) the implementation of PBLA has the potential to provide benefits both in terms of experience, motivation, innovation, and improvement of 21st Century vocational school student skills; and (2) PBLA supplementation will be very effective in increasing sudents’critical thinking skills if the teacher can direct students to be able to learn actively through various activities such as stating problems, discussing, arguing, concluding solutions, and evaluating.